Comparison of the effectiveness of the use of graded inquiries in biochemistry learning - Yunita Arian Sani Anwar; Eka Junaidi (Jurnal Pijar Mipa, 2021)
This study aims to compare the effectiveness of guided inquiry, open inquiry, and tiered inquiry in biochemistry learning. The effectiveness is seen from the product-process perspective, i.e., by looking at critical thinking scores and responses ofÃÂ lecturers' teaching activities. This study involved three groups treated with guided inquiry (level 1), open inquiry (level 2), and tiered inquiry (level 1 to level 2). The number of respondents was 72 students spread over the three groups. Before being given treatment, the three groups were tested for prior knowledge, and it was obtained that the three groups had the same initial ability. The research instrument used was critical thinking questions and a questionnaire of responses to the learning process. The results showed that the group with tiered inquiry treatment had the highest critical thinking score, while open inquiry had the lowest score. It is in line with the respondents' responses related to the learning process. Students feel easier and more comfortable in the tiered inquiry process than the guided and openÃÂ inquiries. The results of the Mann-Whitney U test analysis on the three treatments showed that the three groups had significantly different critical thinking scores. It can be concluded that tiered inquiry is more effective in Biochemistry learning than guided and open inquiries.